Tribological investigations into pin-on-disc tribometer under dry sliding conditions at various temperature ranges. (February 2022) - Verma, Jagannath; Nagdeve, Leeladhar; Kumar, Harish
In this research work, the interaction of aluminum alloy (6061) and EN-31 steel is examined, and interaction is studied on the basis of tribological outcomes under dry sliding conditions at various ranges of temperature. The extrusion process is actually an intricate process, which depends on environmental temperature, sliding velocity with respect to the mating part, the type of external shape, wear and coefficient of friction. Here, variables which directly or indirectly influence the interactions are designed for this system in such a manner that the results can be co-related with another system that has equivalent working condition as there in hot forming and cold forming (up to 250°C) of material interactions. The current work is done on a pin which slides on a disc of aluminium alloy 6061 and EN-31 steel set-up. Experiments are carried out under different conditions by using the design of experiments (DoE) for each case. In the first case (Case-I), the disc is steel and the aluminum alloy works as a pin. In the second case (Case-II), the disc is aluminum alloy and steel works as a pin. Henceforth, frictional coefficient and difference in the weight or wear (volume loss) before and after experiment is achieved. Finally, experiments are designed with the help of design tool to optimize the results and execute the different parameters by involving the analysis of variance . Lower wear volume loss is observed in a steel disc compared to the aluminium alloy pin at room temperature.